2022
DOI: 10.1097/gme.0000000000002058
|View full text |Cite
|
Sign up to set email alerts
|

Spine trabecular bone scores and bone mineral density of postmenopausal Taiwanese women

Abstract: Bone mineral density (BMD) and trabecular bone score (TBS) can be used in combination to predict osteoporosis in a greater number of postmenopausal Taiwanese women. Because the incidence of osteoporosis is the highest among older women, clinicians should pay careful attention to TBS degradation among older patients without low BMD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Compared with women, TBS (L 1-4 ) levels did not plateau in Chinese men between the ages of 20 and 74 years. The declines in TBS and BMD were both greater in women than in men, especially after the age of 50 years, which is related to the decline in estrogen levels after menopause (16).…”
Section: Discussionmentioning
confidence: 89%
“…Compared with women, TBS (L 1-4 ) levels did not plateau in Chinese men between the ages of 20 and 74 years. The declines in TBS and BMD were both greater in women than in men, especially after the age of 50 years, which is related to the decline in estrogen levels after menopause (16).…”
Section: Discussionmentioning
confidence: 89%
“…Menopause is known to be associated with bone loss and the development of osteoporosis in women. Previous studies have demonstrated that BMD decreases with age in women older than 50 years, 8 as well as in those with late perimenopause and postmenopause. 13 Consistent with these findings, our study revealed significant associations between both lumbar and femoral neck BMDs and factors such as age, BMI, menopausal duration, and lumbar muscle sizes.…”
Section: Discussionmentioning
confidence: 96%
“…Dual-energy x-ray absorptiometry (DXA) is considered the criterion standard for measuring BMD, and the lowest T-score of BMD at the lumbar spine, femoral neck, or total hip is recommended for diagnosing osteoporosis 5 . Recent meta-analyses have consistently shown a higher prevalence of osteoporosis in postmenopausal women compared with men 6-8 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Because BMD can only be used to assess bone mass but not bone quality, BMD often underestimates the risk of fracture in the population. TBS can be used as an adjunct measure of BMD and as an assessment tool for the risk of osteoporotic fractures [ 9 ]. Higher TBS reflects higher fracture resistance in denser bones.…”
Section: Introductionmentioning
confidence: 99%